K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 1 2022

a) = (x - 2)- y2

= (x - 2 - y)(x + 2 + y)

b) = (x^2 + 6x + 9) - (2y)^2

= (x + 3)2 - (2y)2

= (x - 2y + 3)(x + 2y + 3)

c) = (x - 3y)2 - 62

= (x - 3y - 6)(x - 3y + 6)

24 tháng 10 2018

(4x3 + 2x2 − 1) − (4x3 − x2 + 1)

= 4x3 + 2x2 – 1 – 4x3 + x2 – 1

= (4x3 – 4x3) + (2x2 + x2 ) – (1+ 1)

= 3x2 – 2

Chọn đáp án C

15 tháng 4 2022

cái này mik lm ròi mà bạn

15 tháng 4 2022

https://hoc24.vn/cau-hoi/cho-da-thuc-a-4x3-35x2y2-3x3-35x2y2-7xy-1a-rut-gon-da-thuc-va-tim-bacb-thu-gon-da-thuc.5830672960238

Bài 1: 

a: \(11x^2-6xy-5y^2\)

\(=11x^2-11xy+5xy-5y^2\)

\(=11x\left(x-y\right)+5y\left(x-y\right)\)

\(=\left(x-y\right)\left(11x+5y\right)\)

b: \(4x^3-16x^2+19x-6\)

\(=4x^3-8x^2-8x^2+16x+3x-6\)

\(=\left(x-2\right)\left(4x^2-8x+3\right)\)

\(=\left(x-2\right)\left(2x-1\right)\left(2x-3\right)\)

Bài 1: 

a: \(11x^2-6xy-5y^2\)

\(=11x^2-11xy+5xy-5y^2\)

\(=11x\left(x-y\right)+5y\left(x-y\right)\)

\(=\left(x-y\right)\left(11x+5y\right)\)

b: \(4x^3-16x^2+19x-6\)

\(=4x^3-8x^2-8x^2+16x+3x-6\)

\(=\left(x-2\right)\left(4x^2-8x+3\right)\)

\(=\left(x-2\right)\left(2x-3\right)\left(2x-1\right)\)

5 tháng 10 2021

\(a,=11x^2-11xy+5xy-5y^2=\left(11x+5y\right)\left(x-y\right)\\ b,=4x^3-8x^2-8x^2+16x+3x-6\\ =\left(x-2\right)\left(4x^2-8x+3\right)\\ =\left(x-2\right)\left(4x^2-2x-6x+3\right)\\ =\left(x-2\right)\left(2x-1\right)\left(2x-3\right)\)

Bài 1: 

a: \(11x^2-6xy-5y^2\)

\(=11x^2-11xy+5xy-5y^2\)

\(=11x\left(x-y\right)+5y\left(x-y\right)\)

\(=\left(x-y\right)\left(11x+5y\right)\)

b: \(4x^3-16x^2+19x-6\)

\(=4x^3-8x^2-8x^2+16x+3x-6\)

\(=\left(x-2\right)\left(4x^2-8x+3\right)\)

\(=\left(x-2\right)\left(2x-1\right)\left(2x-3\right)\)

19 tháng 7 2018

a) \(x^2+6xy+9y^2-3\left(x+3y\right)-4=\left(x+3y\right)^2-3\left(x+3y\right)-4\)

                                                                     \(=\left(x+3y\right)\left(x+3y-3\right)-4\)

b) \(x^2-4xy+4y^2-2\left(x-2y\right)-35=\left(x-2y\right)^2-2\left(x-2y\right)-35\)

                                                                         \(=\left(x-2y\right)\left(x-2y-2\right)-35\)